Nutrient Changes with the Growth of Hydroponics Cowpea (Vigna unguiculata) Sprouts - Naik, P.K.; Dhawaskar, B.D.; Fatarpekar, D.D.; Chakurkar, E.B.; Swain, B.K.; Singh, N.P. (Indian Journal of Animal Nutrition, 2018)
Hydroponics cowpea (Vigna unguiculata; DU-3) sprouts were produced daily for a period of 15 days in a hydroponics chamber (greenhouse) equipped with automatic sprayer of tap water. Cowpea with seed rate of 2.54 kg/m2 with replicates of 15 were soaked in tap water individually for 4 h. Then, the seeds were strained and spread in the greenhouse trays. Inside the greenhouse, each replicate was allowed to grow up to 6 days after which it was harvested. The fresh yield (kg/kg seed) of hydroponically sprouted cowpea increased while that DM yield decreased (P<0.05) with the advancement of growing period and respective values remained highest and lowest at 6th day (6.75 and 9.32 kg) of growing period. The CP% of the hydroponics cowpea fodder was the lowest (P<0.05) on 1st day (21.04), then increased and was the highest on 6th day (27.16%) day of sprouting period. The EE content increased and was the highest on 5th (1.69%) to 6th day (1.77%) of sprouting. During growth period of the hydroponics cowpea sprouts, the CF content increased and NFE level decreased. There was an increasing trend in total ash content of the hydroponics cowpea sprouts with the advancement of the growth period which was the lowest on 1st day (3.40) and the highest (4.44) on 6th day, however, the AIA content was not affected with the advancement of growing period. It could be concluded that cowpea (Vigna unguiculata; DU-3) could be sprouted hydroponically for 6 days to use as feed supplement for dairy animals, however, in vivo trials are required.